The emergence and development of the institution of recognition and enforcement of foreign arbitral awards - Sarina, S.A.; Akimbekova, S.A. (Bulletin of the Karaganda University “Law Series”, 2019)
Regulation of private law relations complicated by a foreign element in the form of recognition and enforcement of foreign judicial and arbitral decisions is the direct responsibility of the state and arises from the need to protect personal and property rights and interests of individuals and organizations that have been taken under state protection. Any state has the exclusive right to exercise jurisdiction within the limits of its territory. Execution in the sovereign territory of acts adopted in other jurisdictions, including foreign judicial and arbitral awards, is allowed to the extent determined by the state itself in the norms of legislation and international treaties, through the recognition of such acts of legal force and legal consequences, as well as through expression of consent to the use of the enforcement mechanism. The article is devoted to the institution of recognition and enforcement of foreign arbitral awards, namely, its emergence and development. However, in order to get a correct understanding of the origin and development of modern arbitration in general and the institution of recognition and enforcement of foreign arbitral awards in particular, it is necessary to pay also some attention to their history. Today, the institution of recognition and enforcement of foreign arbitral awards plays a major role in ensuring the enforcement of judgments made by arbitration.